Interferência de óleos essenciais na oviposição de Neoleucinodes elegantalis (Guenée) (Lepidoptera: Crambidae) e seletividade sobre Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - Leão, Maria Dalila Martins (2022)
In recent decades there has been growing interest in the use of botanical insecticides, especially essential oils with repellent and/or insecticidal activity. The little fruit borer, Neoleucinodes elegantalis (Guenée) (Lepidoptera: Crambidae), is one of the main pests in Solanaceae, being responsible for losses that can reach 100%, and has been basically controlled with chemical insecticides, often used indiscriminately. Thus, research that seeks tools to help control this pest is essential, such as the integrated use of essential oils and the egg parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae), which can optimize management and, consequently, improve the percentage of control of this pest in the field. The objective of this work was to evaluate the potential of three essential oils: rosemary-pepper Lippia origanoides Hunth. (Verbenaceae), citronella Cymbopogon winterianus Jowitt (Poaceae) and lemongrass Cymbopogon citratus (DC) Stapf. (Poaceae), at concentrations (0.1; 0.5; and 1.0%) in altering the oviposition behavior and causing repellency of N. elegantalis in jiló fruits, Solanum aethiopicum L. (Solanaceae), as well as, to evaluate the selectivity of the three essential oils on T. pretiosum. The bioassays were implemented in a completely randomized design (DIC). For the repellency tests, the adult females of N. elegantalis were exposed to jiló fruits treated with the three essential oils in the three concentrations and the control, each treatment was offered individually, evaluating the existence and the preference of oviposition of the pest. In the selectivity bioassays, eggs of the alternative host Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) were used, immersed for 5 seconds in the mentioned treatments, evaluating the effects of essential oils on pre-parasitism (offering alternative host eggs previously immersed in the sprays) and post-parasitism (when parasitized eggs were immersed in treatments at different stages of parasitoid development). All oils promoted deterrence action in the three concentrations, especially rosemary-pepper and citronella, which at the lowest concentration significantly reduced the oviposition of females. Rosemary-pimenta and lemongrass were selective only at the concentration of 0.1% in the egg and pupae stages; citronella at a concentration of 0.1% in the larval and pupal stages. The essential oils of rosemary-pimenta, lemongrass and citronella caused interference in the oviposition behavior of N. elegantalis, however it was observed that they can be harmful to the parasitoid T. pretiosum.